2004
DOI: 10.1097/01.shk.0000132487.89800.15
|View full text |Cite
|
Sign up to set email alerts
|

N??-NITRO-l-ARGININE METHYL ESTER EFFECTS ON NEUTROPHIL FUNCTION AND BACTERIAL CLEARANCE

Abstract: Nitric oxide synthase (NOS) inhibitors are considered promising as a therapeutic option in severe septic shock. The aim of this study was to investigate the effects of N-nitro-L-arginine methyl ester (L-NAME) application on neutrophil (PMN) respiratory burst, phagocytosis, and elimination of Escherichia coli from blood and tissue in rabbits. Twenty-eight female chinchilla rabbits were randomized to a treatment and control group. To quantify the bacterial clearance process, 10 colony forming units (CFU) of E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The latter was confirmed by our tests of three different NO donors. Some studies have actually reported inhibition of the oxidative burst in macrophages by NO donors (Lee et al 2002;Von Knethen and Brune 2002), even in vivo (Stehr et al 2004). Indeed, evidence suggests that iNOS induction is secondary to the respiratory burst (Fries et al 2003;Alblas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was confirmed by our tests of three different NO donors. Some studies have actually reported inhibition of the oxidative burst in macrophages by NO donors (Lee et al 2002;Von Knethen and Brune 2002), even in vivo (Stehr et al 2004). Indeed, evidence suggests that iNOS induction is secondary to the respiratory burst (Fries et al 2003;Alblas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have actually reported inhibition of the oxidative burst in macrophages by NO donors (Lee et al. 2002; Von Knethen and Brune 2002), even in vivo (Stehr et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell analysis was performed by laser flow cytometry. The method of the quantitative assay for monitoring the oxidative burst has previously been described in detail 15, 17…”
Section: Methodsmentioning
confidence: 99%
“…Although both iNOS and nNOS have been implicated in several disease states, NOS inhibitors are not currently used for the treatment of any disorder, and studies that have examined the use of NOS inhibitors have not demonstrated therapeutic efficacy [41]. In addition to inhibiting the beneficial effects of NO, one possible explanation is the lack of isoform selectivity of the NOS inhibitors that have been examined to date.…”
Section: Nos Inhibitors In No-related Diseasesmentioning
confidence: 98%